2019
DOI: 10.1001/jamaneurol.2018.3553
|View full text |Cite
|
Sign up to set email alerts
|

Association of Severe Hydrocephalus With Congenital Zika Syndrome

Abstract: IMPORTANCE Hydrocephalus is a treatable but potentially fatal complication that has not been previously described in congenital Zika syndrome (CZS).OBJECTIVE To describe the clinical features and imaging findings in 24 patients with congenital Zika syndrome (CZS) who developed hydrocephalus. DESIGN, SETTING, AND PARTICIPANTSThis case series included patients with hydrocephalus who were born in October and November 2015 and followed up until mid-2017 in the 2 largest national referral centers for CZS in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…The clinical and neuroimaging protocol is part of a more comprehensive study, and the findings are described elsewhere. 9,11,13 The inclusion criteria were:…”
Section: Patientsmentioning
confidence: 99%
“…The clinical and neuroimaging protocol is part of a more comprehensive study, and the findings are described elsewhere. 9,11,13 The inclusion criteria were:…”
Section: Patientsmentioning
confidence: 99%
“…4) and are difficult to differentiate from periventricular cysts [21,[24][25][26][27][28][29][30][31][32][33][34][35]. Hydrocephalus van der Linden et al [38] described that hydrocephalus is a complication of SCZ in at least a proportion of patients. In this study, 14 of 24 children with CZVS (58%) evolutionarily followed showed signs and symptoms suggestive of hypertensive hydrocephalus, characterized by vomiting, irritability, and/or sudden increases in head circumference percentile, with 2 of these patients (8%) evolving with age-appropriate head circumference.…”
Section: Periventricular Septationsmentioning
confidence: 99%
“…van der Linden et al [38] also suggested that the progressive increase in CSF pressure may contribute additional harm to the CNS and cause stretching and loss of brain mass directly as a result of both its physical compressive effect and by opposing or overcoming blood perfusion pressures. In this context, the main mechanisms that physiologically regulate the turnover of CSF (including its production at choroid plexuses, venous absorption by dural Pachionian granulations, the inflow of CSF through the periarterial pathway toward the neuropil, and the outflow of CSF and interstitial fluid throughout the paravenous vessels pathways of the lymphatic system would hardly be impaired because of the progressive regression of brain mass structures as a whole.…”
Section: Periventricular Septationsmentioning
confidence: 99%
See 1 more Smart Citation
“…У них отмечена грубая задержка психического развития, у больных с выраженной активной водянкой головного мозга диагностировалась в 2 раза меньше, чем у детей с пассивной резидуальной формой ВГ с полидисгинезиями головного мозга (P<0,01). Все данные подтверждаются и исследованиями ряда зарубежных авторов [9][10][11][12][13][14].…”
Section: бюллетень науки и практики / Bulletin Of Science and Practiceunclassified